Electrical properties of monoazacrown ether-substituted phthalocyanines - Öztürk, Z.Z.; Musluoğlu, E.; Ahsen, V.; Gül, A.; Bekaroğlu, O. (Springer Science and Business Media LLC, 1992)
D.c. conductivities of polycrystalline monoazacrown ether-substituted phthalocyanines (M=2H, Ni, Zn, Pb, Cu) and diphthalocyanine (M=Lu) are measured as Au-MPc-Au sandwiches to be of the order 10−10–10−12 S m−1. Chemical doping with oxidants (e.g. NOBF4) and enhancing the stacking of planar phthalocyanine moieties through the formation of alkali metal adducts with sodium and potassium ions leads to increase in conductivity of the order 101–102. The low conductivity and the diamagneticity of the bis(phthalocyaninato)-lutetium can be ascribed to the lack of radical nature in LuH(Pc)2. For the a.c. conductivities, lead and lutetium complexes form a group with higher conductivities and the rest show lower conductivity. The conduction activation energies calculated from Arrhenius plots exhibit the lowest value (0.40 eV) for the lutetium compound.